Indicators of technical actions and intensity according to players' positions in official matches of the brazilian basketball league - J.F. Daniel; P.C. Montagner; C.R. Padovani; J.P. Borin (Federación Extremeña de Balonmano; University of Extremadura, 2016)
Abstract The aim of this study was to analyze indicators of technical actions (ITA) and intensity according to the players positions in six official matches of the Brazilian Basketball League. Ten elite basketball male players participated in this study (27.60±5.54years). The total frequency of matches' indicators (∑MI - sum of all matches indicators of each athlete included in the stats) and the efficiency ratio (ER) from matches' official stats were the ITA considered. To check the intensity, athletes played with HR transmitter. Were produced descriptive measures; and the magnitude of difference (Δ%) between ∑MI and ER second player [Δ%=(1-(ER÷∑MI))*100] was calculated. It was observed that when players were classified by Δ% they were automatically classified by their respective positions in 80% of cases. Players' positions 4 and 5 work closer to the basket and perform the safest and most efficient team play; players' position 1 plays facing to the basket, organizes the collective game, has the largest ball possession volume which can also enable a safer game. Players' position 5 had higher Δ% between ∑MI and ER, representing safer and efficient game; older players had lower intensity; and the basketball game was developed on average slightly above the lactate threshold HR.